Haiti: Sustaining Partnerships in Sustainable Development - Anthony Vinciguerra (The University of Alabama, 2022)
How can universities organize their international community engagement to optimize both student learning and community impact? This article describes the St. Thomas University/Port-de-Paix, Haiti, Global Solidarity Partnership, and provides one model of how a project-focused scaffolding of engaged scholarship opportunities can enhance student learning, empower local communities, and support longterm development.